ON THE STATE OF LEGAL SUPPORT OF CRYPTOCURRENCIES IN UKRAINE: THROUGH THE PRISM OF FOREIGN EXPERIENCE - V.A. Ustymenko; N.Yu. Polishchuk (Економіка та право, 2018)
The development of information technologies is accelerated in the modern world. The digitization of socio-economic relations is carried out on the basis of peer-to-peer blockchain technology. Bitcoin is a cryptographic protocol. The article shows that, to date, there is no common understanding of Cryptocurrency, in some sources they are treated as currency and other goods or raw materials in other. At this moment, cryptocurrency in Ukraine is not regulated at all. This article discusses the potential legal classification of Bitcoin and the consequences thereto. Bitcoin has been, and continues to be, used by some for the purchase of illegal substances and in furtherance of crimes. Nonetheless, Bitcoin possesses significant economic upside over traditional currencies and methods of transaction online. The National Bank of Ukraine (NBU) has not yet recognized bitcoin or other encrypted currencies. Several bills to regulate encrypted money have been submitted, but none has yet been passed. The Ukrainian parliament has been actively trying to find a solution for creating a legislative and regulatory framework specific to the cryptocurrency industry. Ukrainian draft laws give their own definition of crypto-currency, mining and other specific terms; stipulate those who have the right to engage in mining, how the activities of exchanges are regulated, and the attendant moments, such as legal responsibility and specific taxation. Yet, the proposed legislation has not yet been passed into the law. Ukraine should monitor world trends and not miss a chance to use new technologies and innovations in the financial sector. On the basis of the analysis of domestic and foreign practices, a number of non-regulated by Ukrainian law of the creation and circulation of cryptocurrencies have been identified by the law of Ukraine, proposed ways of resolving issues of determining their legal nature and legal regulation. The situation regarding the definition of legal status of cryptographic goods in foreign countries and Ukraine is analyzed. The main points to be solved in the course of approval of the right regulation of cryptocurrencies in Ukraine are determined.